2006
DOI: 10.2116/analsci.22.557
|View full text |Cite
|
Sign up to set email alerts
|

Large-Volume Sample Sweeping with a High Theoretical Plate Number Using a Coupled-Capillary in Capillary Electrophoresis

Abstract: Experimental ApparatusThe violet-LED (light-emitting diode) light source (∼2 mW), CE set-up and data-acquisition system used were similar to that described previously, 10 and are abbreviated herein. A large-volume sample injection (> 5 µL) with an extremely high theoretical plate number (N > 10 7 ) was achieved when the sweeping-MEKC mode and a coupled-capillary (100 -50 µm i.d.) were simultaneously used in a capillary electrophoresis (CE) separation. A low-cost and compact violet-LED (∼2 mW) was used as the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The contributions toward the use of LED‐induced fluorescence detection in MEKC in the period covered by this review are essentially those reported by Li et al 28, 30, 147. Thus, blue (476 nm) 28, violet (410 nm) 30 and UV (380 nm) 147 LEDs have been used for the determination of phenethylamine designer drugs with FITC, dopamine and norepinephrine with NDA, and tryptophan with phenylglyoxal, respectively. In all cases, on‐line sample concentration techniques were used to improve sensitivity.…”
Section: Detection Techniquesmentioning
confidence: 83%
See 2 more Smart Citations
“…The contributions toward the use of LED‐induced fluorescence detection in MEKC in the period covered by this review are essentially those reported by Li et al 28, 30, 147. Thus, blue (476 nm) 28, violet (410 nm) 30 and UV (380 nm) 147 LEDs have been used for the determination of phenethylamine designer drugs with FITC, dopamine and norepinephrine with NDA, and tryptophan with phenylglyoxal, respectively. In all cases, on‐line sample concentration techniques were used to improve sensitivity.…”
Section: Detection Techniquesmentioning
confidence: 83%
“…As stated above, little work has been conducted to improve the phenomenon of sweeping; thus, the contributions have mainly been focused on the analytical use of this on‐line concentration technique. In most cases the protocol for sweeping neutral and anionic analytes uses anionic micelles like SDS and suppressed EOF in a low pH BGE provided by phosphoric acid or phosphate buffer (pH 2–3) 26–32. Under suppressed EOF conditions, other anionic surfactants, di(2‐ethylhexyl) sulfosuccinate and Brij‐S, and cationic ones, CTAB, octyltrimethylammonium bromide and tetradecyltrimethylammonium bromide, have also been used as alternatives for SDS, but with lower enhancement factors 33.…”
Section: Approaches For Improving Sensitivitymentioning
confidence: 99%
See 1 more Smart Citation